Authorship and Authority in the Classicist/Romantic Quarrel. (8th June 2018) - Camilletti, Fabio
Abstract: The Classicist/Romantic quarrel enflaming Italy from 1816 to circa 1830 is not only a confrontation between two literary schools, but also a conflict between two models of authorship, which, in turn, embody two different modalities of authority. By arguing that the Classicist/Romantic quarrel can be read as Italy's post-revolutionary Bildungsroman, fulfilling the function played in France by Stendhal's novels or by Biedermeier literature in Germany, this essay shows how it leaves as a legacy, to the Italian long nineteenth century, a paradoxical coexistence of normativity and unruliness, antiquity and modernity, autarchic drives and openings to foreign culture.